Flow-Through Chloroquine Sensor And Its Applications In Pharmaceutical Analysis. - Saad, Bahruddin; Mohd Zin, Zainiharyati; Jab, Md Sariff; Ab Rahman, Ismail; Saleh, Muhammad Idiris; Mahsufi, Shariff (2005)

(untitled)
Poly(vinyl chloride) membrane electrodes that responded selectively towards the antimalarial drug chloroquine are described. The electrodes were based on the use of the lipophilic potassium tetrakis(4-chlorophenyl)borate as ionexchanger and bis(2-ethylhexyl)adipate (BEHA), or trioctylphosphate (TOP) or dioctylphenylphosphonate (DOPP) as plasticizing solvent mediator.